Model of Hydraulic Conductivity, Infiltration Rate, and Permeability at Gold Mine Waste Dump in North Sulawesi, Indonesia - Friska Agustin; Landy Pratono; Rian Andriansyah; Nofrohu Retongga; Emi Prasetyawati Umar (Journal of Earth and Marine Technology (JEMT), 2023)
The research area is a gold mine operating in North Sulawesi. The aim of the study was to analyze and calculate hydrological parameters, namely: hydraulic conductivity, infiltration rate, and permeability to find out how strong the soil cover is at one level of waste disposal. The method used is the Measurement of hydraulic conductivity, infiltration rate, and permeability in the field, analysis, and calculation of hydraulic conductivity, infiltration rate, and permeability based on field data. In the designated regions of the waste dump, specifically areas 1a, b, and c, we observed certain hydrological patterns that are worth noting. Firstly, the hydraulic conductivity in these areas, which is a crucial determinant of the rate at which water can move through the soil, consistently showcased low average values. This is further supported by the similarly slow infiltration rate identified in the same zones. The ability of the soil to transmit water, i.e., its permeability, also followed this trend, with values leaning towards the lower end of the scale, indicating very slow permeability. One major contributory factor to these patterns appears to be the soil's composition. Predominantly made up of sandy loam, the soil in these areas exhibits high water retention capabilities. Sandy loam, by its nature, binds and retains water effectively, which could potentially explain the observed hydrological behaviors in waste dump areas 1a, b, and c.